Understanding working from home (wfh) behavior of employees in jakarta during the covid-19 outbreak - Tobing, Martha Aprina; Hendarman, Achmad Fajar (Journal of Business and Management, 2020)
Abstract. The COVID-19 outbreak made a new trend in the world of work which is Working from Home (WFH). Despite the companies’ readiness, employers were taking the risk to start WFH including Indonesian companies. WFH practices changed the working environment which affects the workers’ working behavior. This research aims to understand the working environment changes and the working behavior while practicing WFH due to the pandemic. In this study, the researcher conducted in-depth interviews with 10 Indonesian workers in Jakarta from various background to explore the elements of working environment and their working behavior during WFH. Researcher used the Qualitative Coding analyzing the findings. The result shows that there are five significant working environment changes such as; work procedure, compensation adjustment, supervisor support, workspace and HR employee support program. Hence, there are five dimension of working behavior that was found from the Indonesia workers during the WFH; personal discipline, personal resilience, personal effort, social awareness, and coordination and team collaboration. There are two recommendation provided such as; employers should create a structured work system for WFH, and a New Normal Policy based on the Government’s regulation.Keywords: Working from Home, COVID-19 Outbreak, Working Behavior, Working Environment,Qualitative Approach